New algorithm of injection PRP - therapy in parodontology - Biloklytska, G. F.; Kopchak, O. V.; Dieiev, V. A.; Rozdobudko, N. I. (Journal of Education, Health and Sport, 2017)
A step-by-step algorithm of a dentist’s actions directed to platelet autoplasma obtaining for the further therapy of periodontal diseases with platelet-rich plasma (PRP) has been developed on the basis of laboratory and clinical data. The method consists of preclinical (laboratory) and clinical stages. On the basis of laboratory data and coefficient of platelet concentration the authors developed mathematical formulas which allow to calculated an individual volume of autoplasma for a single injection, its total volume, the number of test-tubes necessary as well identify indications and contraindications for the method. The use of the method developed will improve the quality of the patients with multisystem periodontal disease treatment due to optimal stimulation of periodontal tissues regeneration.